An investigation into the construction(s) and representation(s) of masculinity(ies) and femininity(ies) in 1 Corinthians - Jodamus, Johnathan (Department of Religious Studies, 2016)
With the use of SRI as an interpretive analytics combined with a gender-critical hermeneutical optic I have traced out some of the ways in which gender is constituted and performed in the discourse of 1 Corinthians. I demonstrate that normative and normalising engendering is operative in the text and that the discourse replicates hegemonic gendered structurings and machinations from the broader social and cultural environment of that milieu. As a result Christian bodies are scripted to perform according to the dominant cultural protocols and engendering praxes. Because Paul is structured by and functions within the larger discourses of the ancient Mediterranean sex and gender system(s), one cannot comprehend the gendered rhetoric of 1 Corinthians without recourse to its interconnections with ancient gender discourses in general. Furthermore, when Paul is engaged in persuasion through the discourse of 1 Corinthians, gender construction(s) and representation(s), because of the nature of gender in the ancient world, is precisely what is at stake. It seems evident that the discourse of 1 Corinthians tendentiously served to maintain and sustain hierarchical gendered relationships between men and women in the church at Corinth that mimicked the normative, androcentric, and kyriarchal power relations from the dominant Graeco-Roman culture. These power dynamics continue to have an effect on many churches today because they understand Scripture to be regulative for Christian practice in our contemporary society in spite of the temporal and cultural separation of our world from that of the world of the New Testament. As a result contemporary churches reproduce gendered power relations that have been established in habitus which in turn enables replicated gendered structurings in society. In this regard the rhetoric of 1 Corinthians may be viewed as a text that functions as discourse in the making and sustaining of gendered and ideological normativities that continue to structure gendered bodies and bodiliness. It should be kept in mind that the structuredness of habitus came into being as the product of reiteration and sedimenting, and its dismantling similarly will come about as a result of reiteration.